Magic Symbols (Charaktêres) on North African Curse Tablets as a Regional Feature - Németh, György (Acta Classica Universitatis Scientiarum Debreceniensis, 2021)
This study examines the practice of magic symbols in North Africa to find out whether there was a regional peculiarity in the use of charaktêres that distinguished this area from other parts of the Roman Empire. Two phenomena appear to be more common in North Africa, though they may also occur elsewhere: first, charaktêres as encrypted names, and second, charaktêres as framing devices. First and foremost, though, some introductory remarks concerning charaktêres in general are made.